Hybridization of Children's Games through the Mediation of Television - Zeynep GÜLTEKİN AKÇAY (Mehmet KURUDAYIOĞLU, 2018)
This study investigates the relationship between children's games and television. Based on the proposition which holds that children's games have been hybridized through the mediation of television, the purpose of this study is to explicate the hybridization of children's games, which started out on their own by replicating the adult world. The study was conducted, using the qualitative ethnographical approach. In the study, answers were sought to questions such as "What is the relationship between children's games and television?" and "Are there any traces of television narratives in children's games?" The research was carried out during the spring semester of the 2015-2016 academic year at nine state kindergartens located in the city of Sivas. It was observed at the conclusion of the study that children produced their games from the popular television stories and characters. Through this finding, it is possible to assert that children's games have become hybridized.